Mass transfer to power law fluids in fluidized beds of large particles - Kumar S.; Upadhyay S.N. (My University, 2025)
Mass transfer in liquid fluidized beds has been investigated by measuring the rate of dissolution of solid particles in demineralized water and 1.0% aq. carboxyl methyl cellulose (CMC) solution. Results for aq. CMC solution are interpreted using the capillary tube bundle approach and are found to be in reasonable agreement with the present as well as previously published Newtonian mass transfer data. © 1980.